THE EFFECTIVENESS OF PORPE METHOD IN STUDENTS’ READING COMPREHENSION OF REPORT TEXT FOR SENIOR HIGH SCHOOLS STUDENTS AT THE TENTH GRADE OF SMA NEGERI 3 NGANJUK IN THE ACADEMIC YEAR OF 2021/2022 - Sari, Indah Permata (STKIP PGRI Nganjuk, 2023)
The objectives of the research were (1) To find out the students’ reading comprehension of report text achievement before using porpe method. (2) To find out the students’ reading comprehension of report text achievement before using porpe method. (3) To find out the significant differences in the students’ reading comprehension of report text achievement before and after using porpe method. The research was quantitative research and used an experimental design. The type of experimental design was used pre-experimental with one group pre-test post-test design and non-probability as the sampling technique that was conducted in SMA Negeri 3 Nganjuk in the academic year of 2021/2022. The population was used whole class of the tenth grade with the total 359 students and X-5 as the sample that consisting of 35 students. The collecting data used documentation and reading comprehension of report text test were analyzed using Paired T-Test with SPSS 18 for windows and N-Gain using Microsoft Excel. The results showed the value of significance (2-tailed) was 0.000 less than the significance standard (0.05) means there were significant differences before and after using porpe method. From the results of N-Gain, it showed an improvement in the students' achievement from 35 students, 21 (60%) students had improvements in the medium category and 14 (40%) students had improvements in the low category. Based on the before and after test results above, it can be concluded that the porpe method was effective for reading comprehension of report text.